(untitled) (Iraqi Journal of Civil Engineering, 2022)
The Impact of silica fume existence and its content with the duration of curing on concrete compressive strength (ordinary and high) has investigated experimentally. Two mixture sets were done in this work to examine the concrete ordinary and high strength. Every set involved four mixtures with varied silica fume proportions as a substitution of cement with (0, 5, 10 and 15 percent). Ninety-six cubes of concrete were prepared and cured by immersion in water to the required age (7, 28, 90 and 150 days). In ordinary concrete and high strength concrete, the results demonstrate that when silica fume used as a substitution with 15 %, the compressive strength of concrete gave the highest value. As compared with concrete having nil content of silica fume, the earned strength for high compressive concrete consisting of silica fume was relatively less than the corresponding ordinary concrete strength. However, continuously curing with water after 28 days produced a considerable increase in the compressive strength of concrete; such an increase in compressive strength was greater in the existence of silica fume